Social Criticism in Indonesian Literary Works during the New Order Era - I Ketut Sudewa (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
The literary works written and published during the New Order era were used as the data in this article. During this era there were many literary works which contained social criticisms towards the New Order government. The study focuses on the literary work in the form of poems, and employed the qualitative research method. The theory of literary sociology was used as the main theory while the structural theory and semiotic theory were used as the supporting theories. The social criticisms and meaning which were transmitted by the poets through their poems could be optimally revealed using these theories. The result of the study shows that the poems written by the poets during the New Order era, especially those written by Taufiq Ismail contained a lot of social criticisms; he criticized the law, human rights, politics, education and economy implemented by the New Order government. Such social criticisms were shown through different poetic elements such as the diction, language style, and rhetoric. The social criticisms expressed by Taufic Ismail reflected that Indonesia (the readers) should refer back to the nation’s identity and character as stated in the Five Principles ‘Pancasila’ and the 1945 Constitution.